SIBA AS A CONTEMPORARY FASHION INSPIRATION - Suksa Hanifa, Nidya; Imelda, Desra; Rahmat, Fadri (Runtas : Journal Of Arts And Culture, 2024)
The work entitled "Siba As Inspiration for Contemporary Clothing" was inspired by siba which is found in Minangkabau women's traditional clothing, namely the basiba kuruang shirt. Siba is a piece that is located on the left and right sides of the basiba kurung shirt which functions to increase the looseness of the clothes. The creators design clothes with innovative models into contemporary clothing. Creating this work with the aim of increasing the existence of the basiba kurung shirt and making it attractive to all Minangkabau women, and remaining in line with the Minangkabau adage, namely adat basandi syarak, syarak basandi Kitabullah. The process of embodiment of this work begins with exploration to produce sketches and designs, then the craftsmen carry out embodiments by sewing works using semi-boutique and boutique techniques. Using materials in accordance with the three concepts created. The works created by Siba as inspiration for contemporary fashion are three ready-to-wear works, two ready-to-wear delux works, and one houte couture work with each concept using the same color nuance.